PERANCANGAN PORTAL INTRANET UNSIKA SEBAGAI MEDIA SISTEM INFORMASI KAMPUS (Studi Kasus: Universitas Singaperbangsa Karawang) - Komarudin, Oman; Sulistiyowati, Nina; Heryana, Nono (Majalah Ilmiah SOLUSI, 2012)
Information System Development in a university should be supported by the frame that has been standarized so that future development can be directed toward the gates of information systems. The informations gate developed sould provide links to information systems needed, so that will make easier to control and user access. This research makes a portal of information systems at the University Singaperbangsa of Karawang based on informations systems needs, which are gained from Value Chain Analysis tool. This information systems portal can be applied to the intranet of UNSIKA and will become a frame in developing future information systems. Keywords: portal, intranet, information system